Presencia de la familia Hymenophyllaceae (Pteridophyta) en el Parque Katalapi, Cordillera de Quillaipe, Provincia de Llanquihue, Chile - PARRA, MARIA JOSÉ; ACUÑA, KARINA; CORCUERA, LUIS; RODRÍGUEZ, ROBERTO (Gayana Botánica, 2012)
Three Hymenophyllaceae genera were found in Katalapi Park, Region de Los Lagos, Chile: Hymenoglossum, Serpyllopsis, and Hymenophyllum. While the first two genera are monotypic, the third one is represented by 16 species. In this study, we propose that the Hymenophyllum species that were not found in the area are doubtful for Chile due to the inconsistency of their diagnostic characters. From the conservation point of view of this group, six of the species in the park are classified as vulnerable. Finally, and based on vegetative characters, an identification key for Hymenophyllum genera is given.